(untitled) (World Bulletin of Education and Learning, 2025)
This article examines the artistic, cultural, and pedagogical relationship between traditional and contemporary singing styles in Uzbekistan, focusing on maqom — the classical vocal heritage — and estrada, the popular modern genre. Drawing upon ethnomusicological and sociocultural perspectives, the study explores how globalization, media technologies, and education systems have reshaped vocal performance and artistic identity. Ulmasovich, R. U. (2025). The research argues that while maqom embodies spiritual depth, modal complexity, and collective memory, estrada represents modernization, individuality, and digital innovation. Yuldashev, M. U. (2025). The coexistence of both forms reveals the dynamic balance between tradition and modernity in Uzbekistan’s musical culture.